'Mr. Blue Sky' in the West End: Becoming Musical in Our Ladies of Perpetual Succour. Issue 2 (3rd April 2022) - Inchley, Maggie
Abstract: This article explores the role of music in forms of 'becoming' in the adaptation of Alan Warner's novel The Sopranos (1998) for the stage by Lee Hall as Our Ladies of Perpetual Succour (2015). Telling the story of six choirgirls' visit to Edinburgh for a choir competition, a musical strain in Warner's novel ameliorates the 'reprofuturity' felt by the girls as a pressure leading with deathly inevitably to maternity and small-town conformity (Freeman 2007). In OLPS, the girls perform their own stories as a 'gig' incorporating both classical music and cover versions of the songs of popular UK band ELO, affording them opportunities to subvert oppressive gender roles, to deploy music's erotic and affective charges, and to become musical dramaturgs of their own stories. As a musical play, the author argues, OLPS was a sonorous and affective event that staged the girls' negotiations with normative pressures through flows of desire which were immanent, fluid and ongoing. Within theatre's neoliberal and patriarchal economies, its performers deployed musical practices in ways that realized a sense of their own creative potential. In addition to drawing from the materialist feminism of Rosi Braidotti (2002) for its working definition of 'becoming', the article uses approaches from feminist and queer musicologists (McClary 1991: Citron 1993; Cusick 2003; Peraino 2013) to explore music's embodying, relational and temporal processes. In so doing, it points to the usefulness of feminist and queer musicology to performance studies in regard to its interest in the staging of subjectivities and social relations.